Pengaruh Literasi Keuangan Syariah, Nisbah Bagi Hasil, dan Kualitas Pelayanan terhadap Keputusan Menabung - Nurul Kolisoh, Siti; Fitriani, Fitriani; Septiani, Ana (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the influence of sharia financial literacy, profit sharing ratio, and service quality on saving decisions at the Sejahtera Mandiri Syariah Cooperative in Pesawaran Regency. This study uses a quantitative approach using multiple linear regression methods and processed using SPSS 25. The sample in this study was 97 respondents who were new KSMS customers in the 2022–2024 period, taken using purposive sampling techniques and calculations based on the Slovin formula. The results of the study show that partially and simultaneously, Islamic financial literacy, profit sharing ratio, and service quality have a significant effect on customer savings decisions.